Psychosocial and psychoeducational group program for main caregiver of mentally sick in early phase of schizophrenia - Estíbaliz Amaro Martín (Fundación para el Desarrollo de la Enfermería, 2012)
Deinstitutionalization processes in recent times have led to a new age in relations between family and mental health professionals. Care professionals were replaced, after the psychiatric reform, for care carried out by the family without the knowledge, information and skills to assume these functions. This is the situation of many families of patients with schizophrenia.Disabling features of schizophrenia usually cause depends on their families, who take care with the consequent impact on their lives. Psychosocial interventions assessing their work and want to build an alliance with them by giving them skills and coping mechanisms to reduce adverse family atmosphere, anticipate and solve problems and reduce the expressions of anger and guilt keeping appropiate expectations. However, these actions must be enforced by providing main caregivers with the skills that enable them to gain control, this is the main target of psychoeducational programs.Today there are many people in favour of such interventions in the early stages of schizophrenia. However, it is no clear how far development of these programs is supported by evidence of effectiveness. So it has proposed a psychosocial and psychoeducational program aimed at main caregivers of patients with schizophrenia in early stages. This program will be led by a psychiatric nurse in collaboration with other professionals in the interdisciplinary team; psychiatrist, clinical psychologist and social worker. It has developed clinical trial with a control group who will receive the gide for families, caregivers and people affected, "Cómo afrontar la esquizofrenia," and an experimental group will receive, in addition to the guide, the group intervention sessions.